Description of mature larvae of the genus Austrelmis Brown from Argentina (Insecta: Coleoptera, Elmidae) - Archangelsky, Miguel (2016)
Mature larvae of two species of the riffle beetle genus Austrelmis Brown are described and illustrated for the first time: Austrelmis catamarcensis Manzo and Archangelsky and Austrelmis talampayensis Manzo and Archangelsky. A larval diagnosis for the genus is presented; larvae of both species are compared with each other and with two other previously described and illustrated Austrelmis larvae.